Leiomyosarcoma of the left atrium - Čanádyová, Júlia; Šetina, Marek; Smetanová, Simona; Mokráček, Aleš (Asian cardiovascular & thoracic annals, 2008)
A 41-year-old woman underwent successful excision of a leiomyosarcoma of the left atrium. The preferential left atrial location and frequent myxoid appearance of leiomyosarcoma of the heart make it particularly difficult to distinguish preoperatively from atrial myxoma. Early diagnosis and aggressive surgical intervention with chemotherapy may improve the prognosis.
Keywords: dospělí; ifosfamid; pozitronová emisní tomografie; Echocardiography, Transesophageal; Heart Neoplasms; Humans; diferenciální diagnóza; Heart Atria; Myxoma; Positron-Emission Tomography; nádory srdce; Cardiac Surgical Procedures; Ifosfamide; Chemotherapy, Adjuvant; kardiochirurgické výkony; alkylační protinádorové látky; echokardiografie transezofageální; leiomyosarkom; myxom; Adult; Diagnosis, Differential; Leiomyosarcoma; srdeční síně; ženské pohlaví; lidé; adjuvantní chemoterapie; Antineoplastic Agents, Alkylating; Female